The problems that lead to the differential equation and the ways to solve them - A.Turgunov,; M.Askaraliyeva, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article covers the simple issues that lead to differential equations and the ways to solve them, and provides solutions to issues and examples related to them.